(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Education plays a fundamental role in social and economic progress, as well as character development. However, the success of this process is highly dependent on the supportive environment in which students learn. This study aims to examine in depth the influence of the school environment, encompassing physical, academic, and social aspects, on student learning outcomes at the junior high school (SMP) level. The method used was a literature review with a descriptive qualitative approach. Ten relevant scientific articles published between 2020 and 2025 were analyzed to understand the relationship between school environment variables and learning outcomes. The results indicate that the school environment makes a significant and positive contribution to junior high school student learning outcomes. An adequate physical environment, a conducive academic climate, and harmonious social relationships have been shown to progressively increase student interest, engagement, and academic achievement. These findings indicate that the school environment is a strategic investment in achieving educational goals. Therefore, creating a safe, comfortable, and supportive school environment should be a top priority for educators and stakeholders to optimize student potential and continuously improve the quality of learning. Therefore, efforts to create a positive, safe, and supportive school environment are a priority for educators and education stakeholders in order to improve the quality of learning and student learning outcomes.